2010
DOI: 10.1016/j.compositesb.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the crushing performance of hollow and foam-filled small-scale composite tubes with different geometrical shapes for use in sacrificial cladding structures

Abstract: This paper presents the quasi-static crushing performance of nine different geometrical shapes of smallscale glass/polyester composite tubes filled with polyurethane closed-cell foam for use in sacrificial cladding structures. The effect of polyurethane foam on the crushing characteristics and the corresponding energy absorption is addressed for each geometrical shape of the composite tube. Composite tubes with two different thicknesses (1 mm and 2 mm) have been considered to study the influence of polyurethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 22 publications
1
23
0
3
Order By: Relevance
“…The 3D composite samples were tested by a quasi‐static axial compression test between two flat aluminum platens; the top one is static and the bottom one moving with constant speed . The platens were kept parallel to each other throughout the test.…”
Section: Methodsmentioning
confidence: 99%
“…The 3D composite samples were tested by a quasi‐static axial compression test between two flat aluminum platens; the top one is static and the bottom one moving with constant speed . The platens were kept parallel to each other throughout the test.…”
Section: Methodsmentioning
confidence: 99%
“…Because of high specific strength and stiffness, multilayered composite structure has become an important role for many applications in the aerospace and automobile industries, petrochemical and transportation, civil engineering, machinery, etc. (Bambach & Elchalakani, 2007;Mutasher, 2009;Palanivelu et al, 2010;Perillo & Echtermeyer, 2013;Tohmyoh et al, 2011;Zhang & Gu, 2012). However, multilayered cylindrical structure still has a poor performance in the aspect of torsion resistance, and the torsional capacity of multilayered pipe needs to be improved (Debruyne, Vandepitte, & Moens, 2015;Lakreb, Bezzazi, & Pereira, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to thinwalled composite tube, the composite foam sandwich pipes have better local flexural rigidity due to the relative larger thickness-radius, and the local flexural rigidity takes full advantage of the high strength of the composite material [3]. In addition, because the foam has excellent qualities of impact resistance and energy absorption, the composite foam sandwich pipe exhibits better anti-explosion and anti-shock properties [4,5].…”
mentioning
confidence: 98%
“…Tarlochan et al [3,6] reported a kind of tubular composite sandwich structures, which were fabricated from glass fiber, polystyrene foam and epoxy resin and by hand lay-up technique; its quasi-static compression test indicated that the primary mode of failure was progressive crushing with the composites exhibiting high energy absorption capabilities and high crushes force efficiency. Palanivelu and Vantomme [7] conducted a series of tests on the axial compression of unidirectional glass fiber composite tubes filled with polyurethane foam tubes, and they discovered that foam delays the failure of the composite tube fiber under pressure and improves the ultimate load bearing capacity under axial compression.…”
mentioning
confidence: 98%